Incidence Progression and Epidemiological Study of Oral Precancerous Lesions: An Original Research - Monalisha Mahapatra; Kaushal P. Tripathi; Trapti S. Bhadouria; Sathvik Rai; Aakash Malik; Sanchitha Murali; Heena D. Tiwari (Journal of Pharmacy and Bioallied Sciences)
Introduction: Oral precancerous lesions, such as leukoplakia and erythroplakia, are significant contributors to the global burden of oral cancer. Understanding their epidemiology, incidence, and progression is essential to early detection and prevention. In India, these lesions are prevalent due to widespread tobacco consumption and other lifestyle factors, leading to an increased risk of oral cancer development. Methods: A prospective observational study was conducted with 150 patients showing clinical signs of oral precancerous lesions. Three parameters were analyzed: patient demographics, lesion characteristics, and risk factor associations. Incidence and progression data were statistically analyzed using appropriate tests. Results: Our study identified key demographic groups at higher risk, with significant lesion progression in specific subpopulations. Statistical analysis showed strong associations between tobacco use and lesion development, consistent with previous studies. Conclusion: This study highlights the incidence and progression of oral precancerous lesions and their significant correlation with risk factors, emphasizing the need for early intervention strategies.